Anti-Theft ATM Robbery System for Big Video Surveillance using Improved_SVM Algorithm - Pradheepa, R; Priya, V (International Journal of Computer Sciences and Engineering, 2025)
Video survey framework has turned into a basic part in the security and assurance arrangement of urban areas, since Smart Monitoring cameras furnished with canny video examination procedures can screen and pre-alert anomalous practices or occasions. Nonetheless, with the extension of the reconnaissance arrange monstrous observation video information postures colossal difficulties to the examination, stockpiling and recovery in the Big Data time. This paper proposed the new enhanced SVM Algorithm is called IMROVED_SVM. This algorithm shows a novel insightful preparing and usage answer for enormous reconnaissance video information in light of the occasion recognition and disturbing messages from front-end shrewd cameras. The technique incorporates three sections: the astute pre-disturbing for strange occasions, keen stockpiling for observation video and fast recovery for confirm recordings, which completely explores the transient spatial affiliation investigation regarding the unusual occasions in various checking locales. Test comes about uncover that our proposed approach can dependably pre-alert security hazard occasions, considerably diminish storage room of recorded video and essentially accelerate the proof video recovery related with particular suspects